Pengembangan Komik Elektronik (E-COMIC) Usaha dan Pesawat Sederhana Kelas VIII MTs Negeri 6 Bulukumba - Jafar, Andi Ferawati (UIN Alauddin Makassar, 2021)
This research is an R & D (Research andDevelopment) study which aims to describe the process of developing a valid, practical and effective business electronic comic (e-comic) for Business and Simple Aircraft. The development design used is the 4D model (Define, Design, Develop, Disseminate). The subjects of this study consisted of one science subject teacher and 24 class VIII students for the 2019/2020 school year. The research location was located at MT's Negeri 6 Bulukumba, Gantarang District, Bulukumba Regency. The results showed that the validity value obtained for the media was 0.8. This value is in the medium validity range. This shows that the Business and Simple Aircraft e-comics are valid and suitable for use. The level of practicality shows that the Business and Simple Aircraft electronic comics (e-comics) are categorized as practical as indicated by the responses and observations to the implementation of the e-comics of Usaha and Simple Aircraft which provide 100% positive and practical responses. The level of media effectiveness is based on the learning outcomes of students with a percentage of 87% of students who score above the KKM value. Based on these data, it can be concluded that the electronic comics (e-comics) of Business and Simple Aircraft which were developed are valid, practical, and effective.